Chlorophyllide a oxidoreductase Preferentially Catalyzes 8‐Vinyl Reduction over B‐Ring Reduction of 8‐Vinyl Chlorophyllide a in the Late Steps of Bacteriochlorophyll Biosynthesis. (2nd April 2020) - Yamamoto, Haruki; Mizoguchi, Tadashi; Tsukatani, Yusuke; Tamiaki, Hitoshi; Kurisu, Genji; Fujita, Yuichi
Abstract: Bacteriochlorophyll a (BChl) is an essential pigment for anoxygenic photosynthesis. In late steps of the BChl biosynthesis of Rhodobacter capsulatus, the C8 vinyl group and C7=C8 double bond of 8‐vinyl chlorophyllide a (8 V‐Chlide) are reduced by a C8 vinyl reductase (8VR), BciA, and a nitrogenase‐like enzyme, chlorophyllide a oxidoreductase (COR), respectively, to produce 3‐vinyl‐bacteriochlorphyllide a . Recently, we discovered 8VR activity in COR. However, the kinetic parameters of the COR 8VR activity remain unknown, while those of the COR C7=C8 reductase activity and BciA have been reported. Here, we determined the kinetic parameters of COR 8VR activity by using 8 V‐Chlide. The K m value for 8 V‐Chlide was 1.4 μM, which is much lower than the 6.2 μM determined for the C7=C8 reduction of Chlide. The kinetic parameters of the dual activities of COR suggest that COR catalyzes the reduction of the C8 vinyl group of 8 V‐Chlide preferentially over C7=C8 reduction when both substrates are supplied during BChl biosynthesis. Abstract : The nitrogenase‐like enzyme chlorophyllide a oxidoreductase (COR) catalyzes sequential C8 vinyl reduction of 8‐vinyl chlorophyllide a and B‐ring (C7=C8) reduction of chlorophyllide a to produce 3‐vinyl bacteriochlorophyllide a . The enzymatic parameters of these reductions were determined and suggested that COR preferentially catalyzes the former reduction when both substrates are supplied during bacteriochlorophyll biosynthesis.